2015
DOI: 10.1007/s10555-015-9552-6
|View full text |Cite
|
Sign up to set email alerts
|

HER2 expression status in diverse cancers: review of results from 37,992 patients

Abstract: Human epidermal growth factor receptor 2 (HER2) amplification/overexpression is an effective therapeutic target in breast and gastric cancer. Although HER2 positivity has been reported in other malignancies, previous studies generally focused on one cancer type, making it challenging to compare HER2 positivity across studies/malignancies. Herein, we examined 37,992 patient samples for HER2 expression (+/− amplification) in a single laboratory. All 37,992 patients were tested by immunohistochemistry (IHC); 21,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
278
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 371 publications
(291 citation statements)
references
References 47 publications
8
278
2
3
Order By: Relevance
“…Elevated CEP17 count (polysomy) has been linked with adverse clinicopathologic features and HER2 overexpression, although there are numerous discrepancies in the literature (37). HER2 overexpression and/or amplification are recurrently reported in numerous tumor types, and have been shown to have significant therapeutic implications in patients with cancer (33). A meta-analysis of 5,976 patients demonstrated that HER2/neu overexpression was associated with mortality and recurrence in patients with PCa (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated CEP17 count (polysomy) has been linked with adverse clinicopathologic features and HER2 overexpression, although there are numerous discrepancies in the literature (37). HER2 overexpression and/or amplification are recurrently reported in numerous tumor types, and have been shown to have significant therapeutic implications in patients with cancer (33). A meta-analysis of 5,976 patients demonstrated that HER2/neu overexpression was associated with mortality and recurrence in patients with PCa (52).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used immunohistochemical analysis to evaluate HER2 protein expression in primary prostate specimens, demonstrating expression rates ranging from 0-100% (29)(30)(31). Therefore, the exact prevalence of HER2 gene amplifications in primary PCa remains unknown, likely owing to the wide range of antibodies and methods used in these studies (32,33).…”
Section: Her2 Gene Amplification In Patients With Prostate Cancermentioning
confidence: 99%
“…A recent study has evaluated gene amplification and expression status by FISH and IHC in a large cohort of more than 37,000 tumors, in which UC was the most frequently HER2 expressing tumor type of all tested solid tumors [4]. Among 475 examined UC samples, 12.4% strongly expressed HER2 (IHC 3+) and IHC correlated in >90% with positive FISH.…”
Section: Discussionmentioning
confidence: 99%
“…Among the array of responsible genes, one of the most flagrant genetic aberrations was ascribed to HER-2 in GBC [10]. Yan et al [12] reported that HER-2 overexpression was detected predominantly in malignancies of epithelial origin. Furthermore, the availability of FDA-approved agents targeting HER-2-positive malignancies, such as trastuzumab and pertuzumab (humanized monoclonal antibodies) and lapatinib and afatinib (dual EGFR/HER2 inhibitors), makes it a marker of choice for testing in GBC.…”
Section: Introductionmentioning
confidence: 99%